2022
DOI: 10.1038/s41598-022-15250-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electrical, and magnetic properties of nano Sr1−XLaXFe12O19 (X = 0.2–0.8)

Abstract: The current work is mainly devoted to the synthesis, structural, electrical, and magnetic characterization of Sr1−XLaXFe12O19 (X = 0.2–0.8) (SLFO) nanoparticles synthesized via the hydrothermal technique. The hexagonal peaks were determined using X-ray diffraction analysis. The obtained results indicated that the lattice constants were noted to be increasing from 0.58801 to 0.58825 nm (a = b), and 2.30309 to 2.30341 nm (c) with increase of in ‘X’. The morphological studies ensured that the grains as well as na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…The ϵ r value has a very modest rise from 40 to 250 °C and is nearly constant. This is due to weak and constant feedback of the charge carriers at this range of temperatures . Beyond 250 °C, a steep rise of ϵ r is noticed.…”
Section: Resultssupporting
confidence: 91%
“…The ϵ r value has a very modest rise from 40 to 250 °C and is nearly constant. This is due to weak and constant feedback of the charge carriers at this range of temperatures . Beyond 250 °C, a steep rise of ϵ r is noticed.…”
Section: Resultssupporting
confidence: 91%
“…Further, the average grain size was determined using linear intercept method, wherein the formula G avg = 1.5L/MN (where L indicates the test line length, M indicates the magnification, and N indicates the number grains intersecting the test line) was used. [22][23][24] The obtained data confirmed that the G-value was increasing from 96.8 to 117.6 nm with pH. For pH = 10 and 11, the G-values were found to be 106.3 and 112.5 nm, respectively.…”
Section: Surface Morphologysupporting
confidence: 74%
“…The obtained values are almost in good agreement with the crystallite size. This in turn establishes the existence of domain wall rotations, reinforcing the production of coercivity 42 . That means domain wall displacement possesses the low contribution in achieving the H c value.…”
Section: Resultsmentioning
confidence: 83%
“…That means domain wall displacement possesses the low contribution in achieving the H c value. The cation distribution is performed using the two‐sublattice model 42 . This model says that the total n B can be calculated using the formula M = M B – M A (where individual magnetic moment values of A and B sites are measured).…”
Section: Resultsmentioning
confidence: 99%